Профилактика ожирения и неалкогольного стеатогепатита у крыс антидисбиотическим средством = Prevention and treatment effect of antidysbiotic formulation on obesity and nonalcoholic steatohepatitis in rats - Levitsky, A. P.; Tkachuk, V. V.; Velichko, V. I.; Vasyuk, V. L. (Journal of Education, Health and Sport, 2016)
Levitsky A. P., Tkachuk V. V., Velichko V. I., Vasyuk V. L. Профилактика ожирения и неалкогольного стеатогепатита у крыс антидисбиотическим средством = Prevention and treatment effect of antidysbiotic formulation on obesity and nonalcoholic steatohepatitis in rats. Journal of Education, Health and Sport. 2016;6(4):281-286. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50200 http://ojs.ukw.edu.pl/index.php/johs/article/view/3471 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016. УДК 517.112:612.8+615.462 ПРОФИЛАКТИКА ОЖИРЕНИЯ И НЕАЛКОГОЛЬНОГО СТЕАТОГЕПАТИТА У КРЫС АНТИДИСБИОТИЧЕСКИМ СРЕДСТВОМ А. П. Левицкий1, В. В. Ткачук2, В. И. Величко2, В. Л. Васюк3 1ГУ «Институт стоматологии НАМН Украины» (г. Одесса, Украина) e-mail: flavan@mail.ru 2Одесский национальный медицинский университет (Украина) 3Буковинский государственный медицинский университет (г. Черновцы, Украина) Резюме Сочетание высокожирового рациона и кишечного дисбиоза вызывает у крыс развитие ожирения и неалкогольного стеатогепатита (НАСГ). Введение антидисбиотического средства «Квертулин» (кверцетин + инулин + цитрат кальция) предотвращает развитие ожирения и НАСГ. Ключевые слова: ожирение, неалкогольный стеатогепатит, липиды, высокожировое питание, дисбиоз, антидисбиотическое средство. PREVENTION AND TREATMENT EFFECT OF ANTIDYSBIOTIC FORMULATION ON OBESITY AND NONALCOHOLIC STEATOHEPATITIS IN RATS A. P. Levitsky1, V. V. Tkachuk2,V. I. Velichko2, V. L. Vasyuk3 1SE«The Institute of Stomatology of the National academie of medical science of Ukraine» (Odessa, Ukraine) e-mail: flavan@mail.ru 2Odessa National Medical University (Ukraine) 3Bukovina State Medical University (Chernovtsy, Ukraine) Abstract Aim: To determine of prevention and treatment effect of antidysbiotic formulation on obesity and NASH in rats. Methods: The experimental obesity and NASH were induced by feeding rats with a high fat diet (HFD) (fodder, plus 15 % sunflower oil – 40 days) and driaking water with lincomycin at a dose of 60 mg/kg day for 5 days. The duration of experiment was 41 days. One group of rats received HFD and lincomycin, received antidysbiotic formulation Quertulin (quercetine + inuline + Ca-citrate) in dose 300 mg/kg 40 days. Determined morphometric parameters like body mass, body mass index, content of triglyceride (TG) and cholesterine (Ch) of liver and serum cjntent of bilirubine and activity of ALT and in serum, alkaline phosphatase (AP). Results: At obesity and NASH body mass, body mass index, content of TR, Ch, in liver and serum were increased; in serum content to bilirubine and activity to ALT and AP were increased. Taking quertulin normalized morphometric and biochemic indexis in liver and serum. Conclusion: Antidysbiotic formulation quertulin made of prevention and treatment effect on obesity and NASH. Key words: obesity, nonalcoholic steatohepatitis, lipids, high fat nutrition, dysbiosis, antidysbiotic formulation.